“Implementación de un plan de mantenimiento de equipos y maquinaria para la empresa ADROSES”. - Heredia Noroña, Wilmer Fabricio (2022)
The project fulfills purpose a preventive maintenance plan implementing into equipment and machinery, through a study and different elements analysis, whose have the "ADROSES" enterprise, to ensure the post-harvest process continuity and thus, avoiding the corrective maintenance activities excessive use, analyzing the its different sub-processes variables such as: Cutting and Reception, Classification and Packaging. On the other hand, the management for preventive maintenance plan is based on following activities: Facilities identification, process areas, primary equipment and secondary equipment, Critical processes determination, Inspection schedule structuring, protocols before unscheduled events, preventive activities, Maintenance determination indicators establishment and maintenance plan budget structuring. It was developed he initial maintenance indicators identification, such as: Mean Time Between Failures (MTBF), Mean Time To Repair (MTTR) and availability for the packaging thread, resulting the improvement lines opening, whose generate benefits such as: Cost reduction, failures and breakdowns, downtime; by achieving to get more efficient machinery. A preventive maintenance plan implementation seeks to extend the equipment and machinery useful life, by helping to structure and organize information. A maintenance plan use allows better control into relation to failures and breakdowns with the indicators development are increased the machines reliability from 74% to 99.39%, improving their productivity and operating themselves.